Workers' Compensation Analysis for Its Second Century - Dillender, Marcus (W.E. Upjohn Institute, 2017)
This volume represents an effort to draw policy implications from research in three critical performance areas for workers' compensation programs; prevention of disabling injury and disease, return to work performance for injured workers, and the adequacy of compensation for those disabled by their workplace.